Caracterización del contenido estomacal del camarón litopenaeus vannamei durante el ciclo de cultivo en el sector La Pitahaya - Barzola Barzola, María Lorena (2012)
This study allowed us to specifically determine the type of food that is preferentially ingested by the shrimp Litopenaeus vannamei, in such a way can the producer shrimp get a good factor of convertibility, reduce consumption of artificial food, improve survival and growth of animals, reduce production costs by run and quality end product. The samples were obtained from the shrimp Santa Cecilia located at site La Pitahaya in the town of Arenillas in El Oro Province. The analysis of the samples was conducted in the laboratory of Planctonologia located in the Faculty of agricultural sciences of the Machala Technical University, located on the farm Santa Inés 5½ Km via Machala - passage, province of El Oro. In this project she worked in three ponds in which removed a sample of 10 shrimp ponds. The general objective that my question was the following: analyzing the food eaten by the shrimp Litopenaeus vannamei during the crop cycle in the sector the Pitahaya and the specific objectives were: identify qualitatively the food eaten by the shrimp Litopenaeus vannamei. Quantitatively determine the ingested food preferred by the shrimp Litopenaeus vannamei. In the quantitative and qualitative analysis of phytoplankton could be determined that the Chrysophytas (diatoms) are peaking with 93% of preference of the shrimp species that were found were: Amphora graeffi, Amphora ovalis, Cossinodiscus radiatus, Cymbela cistula, Navicula brasiliensis, Navicula palpebralis, Nitzschia angularis, Nitzschia bicarpatarter, Nitzschia closterium, Pinnularia brarunix, Pleurosigna angulatum, Rhizosolenia sp., Thallassiosira similis, followed by the Cyanophytas 7.03% and dinoflagellates with 0.17%. In the quantitative and qualitative analysis of zooplankton could determine the Group of crustaceans as it is the copepod to 94.16% and remains of artemia with 5.8%.